Implikasi Pencegahan ke Luar Negeri bagi WNI yang Terlibat Persoalan Hukum berdasarkan Perspektif Hak Asasi Manusia - Rachman Maulana Kafrawi; Bambang Ariyanto; Kamarudin (Faculty of Law Hang Tuah University, 2021)
The function and role of Indonesian immigration is to prevent, as a traffic controller people enter or leave the territory of the Republic of Indonesia in accordance with what is stated in the Law Law of the Republic of Indonesia Number 6 of 2011 concerning Immigration. This legal research focused on knowing the implications of prevention abroad for Indonesian citizens abroad based on a human rights perspective. The research method used is normative juridical. This research concludes that the regulations in Indonesia which regulate the prevention of Indonesian citizens abroad is in accordance with the values and norms contained in the in the state ideology, namely Pancasila and the state Constitution, namely the 1945 Constitution prevention carried out by immigration officers to people suspected of being involved in cases The law that will go outside the territory of the Indonesian state is in accordance with the applicable rules. Then related to prevention, it is also not a form of limiting human rights, because human rights are Indonesia is a human rights balance with its human obligations as a member of society. The use of human rights in Indonesia cannot be carried out without paying attention to human rights obligations, in other words, human rights cannot be used absolutely.